Gastric neoplasms. Issue 11 (November 2020) - Schiller, Michael P.; Strong, Sean; Wilkerson, Paul M.
Abstract: There are several different types of gastric neoplasm, depending on the cell of origin. The most common gastric neoplasm is adenocarcinoma followed by lymphoma, gastrointestinal stromal tumours (GISTs), carcinoids and other rarer neoplasms. Gastric adenocarcinoma is one of the most common cancers worldwide, especially in the Far East. In the UK, the incidence is lower, but the poor prognosis of late stage disease means the impact on population health is significant. Most patients present with advanced disease at diagnosis. Therefore, primary prevention by modifying risk factors and secondary prevention with early diagnosis have the best chance of improving the grave prognosis. Diagnosis is usually made with endoscopy plus biopsies while staging is complex, consisting of EUS, CT, PET-CT, and staging laparoscopy. Treatment is offered in a stage-related multimodal approach that includes resection (endoscopic, laparoscopic, or open surgery) often with perioperative chemotherapy and systemic therapy depending on stage at presentation. The 5-year overall survival rate in early stage disease is over 80% but all stage 5-year overall survival is less than 20%. GISTs arise from mesenchymal tissue in the stomach and usually have a less aggressive growth pattern, with lower rates of metastasis and direct invasion. Based on staging and pathological factors in the resected specimen, neoadjuvant or adjuvant therapy with tyrosine kinase inhibitors (imatinib) may be offered. Lymphomas and carcinoids have their own aetiology and pathophysiology with according treatments. These cancers rarely require resection.